Factors of effective strategy implementation: Empirical evidence from Slovenian business practice - Tomac Cater; Danijel Pucko (Journal for East European Management Studies, 2010)
The paper's purpose is to add to the body of knowledge on strategy implementation by systematically studying the activities for and obstacles to strategy execution on a sample of 172 Slovenian companies. The results show that managers mostly rely on planning and organising activities when implementing strategies, while the biggest obstacle to strategy execution is poor leadership. Moreover, the results of multiple regression analysis reveal that greater obstacles to strategy execution in the forms of inadequate leadership skills and employees' reluctance to share their knowledge have a negative influence on performance, while adapting the organisational structure to the selected strategy as an activity for strategy implementation has a positive influence on performance. – – Der Zweck dieses Artikels ist, einen Beitrag zur Erweiterung des Wissens über Aktivitäten und die Hindernisse der Strategiedurchführung beizutragen anhand eines Samples von 172 Slowenischen Unternehmen. Die Ergebnisse zeigen, dass sich die Betriebsleiter bei der Implementation von Strategien größtenteils auf Planung und Organisaiton konzentrieren, während das größten Hindernis zur Durchführung der Strategie schlechte Führung ist. Weiter zeigen die Ergebisse der Multiplen Regression auf, dass Hindernisse zur Strategiedurchführung in Form von mangelhafter Fürung und der Zurückhaltung der Mitarbeitern, ihre Kenntnisse mitzuteilen, einen negativen Einfluss auf den Erfolg haben, während die Anpassung der Organisationsstruktur an die ausgewählte Strategie einen positiven Einfluss auf den Erfolg hat.
Keywords: 650; strategy; strategy implementation; activity; obstacle; performance; Slovenia